Desarrollo de barritas de cereales con variedades de quinua (Chenopodium quinoa) empleando aglutinantes naturales - Franco Núñez, Amy Nohely (2023)
The purpose of this research was to develop cereal bars with varieties of quinoa: white, red, and black (Chenopodium quinoa), using two types of natural binders, bee honey, and cocoa mucilage. A completely randomized AxB design was applied, resulting in six treatments and three replicates. Tukey's multiple range test (p ≤0.05) was used to determine the differences between treatments. Physicochemical variables were analyzed (moisture, ash, pH, acidity, ethereal extract, total nitrogen, crude fiber, carbohydrates, and energy-Kcal); where treatments T1, T2, T4 stood out for their protein, fat, and energy content, however, for carbohydrates T5 stood out; while for fiber and ash, no statistical differences were obtained, remaining with values around 3.30% and 1.60% respectively in all samples.